Stephen King'uyu, Ministry of Environment, Water and Natural Resources, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
A 2-day workshop hosted by the CGIAR Research Program on Climate Change, Agriculture and Food Security from 13-14 November, Warsaw, Poland, brought together 37 representatives from 10 different countries across Asia, Africa and Latin America to share their lessons and experiences in developing climate adaptation plans for the agriculture sector. For more information see: "Planning climate adaptation in agriculture" http://ow.ly/qSN00 "New reports highlights lessons from national adaptation planning" http://ow.ly/qSN1h